Now is the Time: Enhancing Access to Midwifery Care in the United States. Issue 4 (July 2020) - Callister, Lynn Clark
Abstract : Midwifery care is not available for all women in the United States. Various barriers exist including an inadequate number of midwives. Unlike other peer high-resource countries, in the United States there are various paths to becoming a midwife rather than a standard training program that involves university education. There are several midwifery credentials, which can be confusing to potential patients, the community, and other health care professionals. Much work is needed to make midwifery care available as a choice for women in the United States. Our global health nursing expert, Dr. Callister, offers a perspective on midwifery in the United States as compared to peer countries.